Molecular Docking, ADME Study, Synthesis, Characterization and Preliminary Antimicrobial Activity Evaluation of New Phenylalanine Derivatives of Sulfonamide - Naeem, Haider Mohsen; Dakhel, Zainab Abdelhadi (Journal of Contemporary Medical Sciences, 2025)
Objective: The main objective for this study is the synthesis of a series of new phenylalanine derivatives of sulfonamide. Methods: The final compounds P1-P4 were synthesized starting with the synthesis of two intermediate compounds Ⅰ and Ⅱ, which were reacted with each other in to get compound Ⅲ. Then, the later was reacted with hydrazine hydrate led to the compound Ⅳ that was eventually reacted with different aldehydes to produce the target compounds. Characterization of their structure was performed using ATR-FTIR and HNMR spectroscopies. The assessment of the antimicrobial activity was done for all of them. The final compounds were subjected to molecular docking and ADME study, which were conducted in comparison to standard drugs (sulfamethoxazole and sulfadiazine). Results: The synthesized final compounds exerted a broad inhibitory activity on certain microbes, including Gram-positive bacteria (Staphylococcus aureus and Streptococcus pneumonia), Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa), and one fungus (Candida albicans). However, compounds P3 and P4 had the highest activity. The molecular docking findings represented compounds P1, P2 and P3 with high docking scores compared with standard drugs, while the ADME study showed a desired drug-likeness and accepted pharmacokinetic properties. Conclusions: The target compounds were successfully synthesized with good antimicrobial activity. The compounds P1, P2 and P3 recorded the highest docking scores, while all the final compounds had good ADME findings.